2013
DOI: 10.1183/09059180.00006313
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance imaging in pulmonary arterial hypertension

Abstract: Cardiac magnetic resonance imaging (CMRI) provides accurate information about right ventricular (RV) mass, RV volumes and other markers of RV function. CMRI is proving to be a particularly useful tool in pulmonary arterial hypertension (PAH), as measures of RV function have been shown to be prognostic of long-term outcomes in this disease. Changes in RV function can also provide important information about a patient's disease course and response to treatment. As CMRI is noninvasive it can be used to regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 54 publications
(68 reference statements)
0
50
0
6
Order By: Relevance
“…In patients with suspected PH, the presence of late gadolinium enhancement, reduced pulmonary arterial distensibility and retrograde flow have high predictive value for the identification of PH; however, no single CMR measurement can exclude PH [60][61][62]. In patients with PH, CMR may also be useful in cases of suspected CHD if echocardiography is not conclusive.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…In patients with suspected PH, the presence of late gadolinium enhancement, reduced pulmonary arterial distensibility and retrograde flow have high predictive value for the identification of PH; however, no single CMR measurement can exclude PH [60][61][62]. In patients with PH, CMR may also be useful in cases of suspected CHD if echocardiography is not conclusive.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…69 A subsequent further increase in RV volumes and a decrease in stroke volume during treatment are clear signs of progressive RV failure and can be observed before failure becomes clinically manifest. 7,12 This is illustrated in Figure 4, which shows a patient with progressive RV dilatation over the years together with a decrease in stroke volume, preceding clinical failure. Close monitoring of RV volumes and function offers the possibility for early therapeutic interventions, but the impact of such a strategy on patient outcomes has yet to be studied.…”
Section: Cardiac Mri Volumetric Measurementsmentioning
confidence: 99%
“…Although echocardiography is the mainstay in the assessment of hemodynamic and ventricular function in PH, MRI has emerged as the gold standard for quantifying volumes, function, and flow in the right side of the heart. [2][3][4][5][6][7] PET is also offering novel insights into perfusion and blood flow, metabolism, neurohormonal activation, and other molecular processes in the right side of the heart but is used mainly for research at this time. Catheterization of the right side of the heart remains the gold standard for defining PH and assessing hemodynamics both at rest and with exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition, CMR offers the possibility to quantify regurgitant volumes, use delayed gadolinium enhancement as a marker for focal scar burden, and to assess myocardial strain, coronary perfusion, and pulmonary pulsatility. 36 One recent study was able to predict survival in patients with PAH based on the RV ejection fraction computed from CMR. 37 A more recent multicenter study demonstrated the feasibility of using CMR to track changes in RV size and function in response to 12 months of PAH-specific therapy.…”
Section: Cardiac Mrimentioning
confidence: 99%